Interpersonal Meaning: Verbal Text-Image Relations in Multimodal Science Texts for Young Children - Maria Koutsikou; Vasilia Christidou; Maria Papadopoulou; Fotini Bonoti (MDPI AG, 2021)
Verbal text and images constitute the principal semiotic modes interacting to produce interpersonal meanings in multimodal science texts for young children. These meanings relate to pedagogical perceptions about children's learning. This study examined verbal text-image relations regarding the interpersonal meaning dimensions of address (the way the reader is addressed), social distance (the kind of the relationship between the reader and represented participants), and involvement (the extent to which the reader is engaged with what is represented) in multimodal text excerpts from science-related books for preschool children. The sample consisted of 300 randomly selected units of analysis. For each unit, the verbal and the visual content was analyzed along each dimension, and the relevant verbal text-image relation was determined. Results indicated that regarding address and involvement, relations of convergence appeared significantly more frequently than relations of complementarity and divergence. Concerning social distance, relations of complementarity and divergence were observed more frequently than relations of convergence. Results are discussed in the context of the Systemic Functional Grammar and the Grammar of Visual Design, in the light of the socio-cognitive perspective on science teaching and learning. Implications for the selection, design, and use of multimodal science texts for young children are also discussed.